POSSIBILITIES OF MULTISPIRAL COMPUTER TOMOGRAPHY FOR PULMONARY SEQUESTRATION DIAGNOSIS - N. V. Agurina; E. I. Zyablova; E. G. Shevchencko; E. P. Yasakova (Инновационная медицина Кубани)
Pulmonary sequestration is a rare abnormality among all congenital defects of pulmonary development. We presented three clinical observations with various clinical manifestations. Possibilities of multispiral CT for the present pathology are described.